PERILAKU GESER BALOK BETON BERTULANG MUTU TINGGI DENGAN VARIASI FLY ASH BATU BARA, PASIR POZZOLAN DAN BONGKAHAN CANGKANG SAWIT - Cut Fatmawati; Teuku Budi Aulia; Muttaqin Muttaqin (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
The utilization of high strength concrete particularly on construction is an option in structural elements. High Strength Concrete (BMT) is a compressive strength exceeding 6000 psi or 41 MPa. High quality concrete can be obtained by mixing superplasticizers (high range water reducers) and cementitious mineral additives in the form of fly ash, pozzofume (super fly ash), and microscopy (silicafume). In this study, it will used the substitution of cement material using coal fly ash, fly ash pozzolan sand and palm shell ash fly ash, fine aggregates using pozzolan sand, coarse aggregates palm shell. The aim of this study is to compare the shear behavior of normal high quality reinforced concrete beams and beams with the addition of material substitution. The high quality reinforced concrete beam specimens were designed to experience shear failure by strengthening the bending area. Reinforced concrete beam specimens of beam size 150 mm x 300 mm x 2200 mm with shear reinforcement diameter 6 mm (fy) 423.46 MPa, compressive reinforcement 16 mm (fy) 412.39 MPa and tensile reinforcement 19 mm (fy) 462, 24 MPa. The beam specimen is pure flexural tensile strength with a size of 150 mm x 150 mm x 600 mm and a cylindrical specimen with a diameter of 150 mm x 300 mm in height. The magnitude of the flexural tensile strength for BMT-N with f cc = 44.4 MPa is 4.5, and for BMT-FBPP with f cc = 51.04 MPa which is 5.35 with FAS 0.3. The results of the two beams experienced shear failure, with a comparison of laboratory and theoretical shear capacity of 2,292 BMT-N with a maximum load of 27,200 MPa, BMT-FBPP 1,720 with a maximum load of 21,410 MPa. The values of deflection and ductility tend to decrease in BMT-FBPP beams which are equal to 19.780% and 6%.